Effect of virtual reality games on stroke patients’ balance, gait, depression, and interpersonal relationships - Song, Gui bin (J Phys Ther Sci, 2015)
[Purpose] The purpose of the study was to determine the effects of training using virtual reality games on balance and gait ability, as well as the psychological characteristics of stroke patients, such as depression and interpersonal relationships, by comparing them with the effects of ergometer training. [Subjects] Forty stroke patients were randomly divided into a virtual reality group (VRG, N = 20) and an ergometer training group (ETG, N = 20). [Methods] VRG performed training using the Xbox Kinect. ETG performed training using an ergometer bicycle. Both groups received training 30 min per day, five times per week, for eight weeks. [Results] Both the VRG and ETG subjects exhibited a significant difference in weight distribution ratio on the paralyzed side and balance ability. Both the VRG and ETG patients showed significant improvement in psychological measures BDI and RCS, after the intervention, and the VRG sowed a more significant increase in BDI than the ETG. [Conclusion] According to the result of this study, virtual reality training and ergometer training were both effective at improving balance, gait abilities, depression, and interpersonal relationships among stroke patients.